Moderasi Beragama Sebagai Upaya Membangun Sikap Toleransi Siswa di SMKN 3 Panyabungan - Nst, Mhd Aji; Mislaini; Ummu Salamah; Santika Dewi; Rahma Atikah; Nurmala Sari; Nurhayati; Siti Rukiah (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to describe the implementation of religious moderation as an effort to foster students' tolerance at SMK Negeri 3 Panyabungan. The background of this research is based on Indonesia's high level of religious diversity, which has the potential to trigger conflict if not accompanied by mutual respect, thus requiring an educational approach that instills tolerance values from an early age. This research employed a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results show that religious moderation in the school environment is implemented through classroom learning, teachers' role modeling, inclusive school policies, extracurricular activities, and social interactions among students that emphasize fairness, respect for differences, and togetherness. This implementation has proven effective in fostering students' tolerance, as reflected in the freedom to practice worship, cooperation across religious backgrounds, and the creation of harmonious social relationships. Therefore, religious moderation can be regarded as an effective character education strategy in building students' tolerance and creating a peaceful, inclusive, and diversity-respecting educational environment